A new record of Sida glutinosa (Malvaceae), a rare species of the Caatinga in northeastern Brazil, with lectotypifications and taxonomic notes on the allied Sida glabra - Baracho, George Sidney; Agra, Maria De Fátima (Phytotaxa, 2016)
Sida glutinosa (Malvaceae), a rare and poorly known species in Brazil, is recorded in areas of the Caatinga ecoregion, as well as its first occurrence in the State of Paraíba. In addition, the relationship between this species and its closest relative, S. glabra, is discussed, S. piauhyensis is lectotypified, and a key to separating the species of Sida sect. Nelavagae in Pernambuco and Paraíba States is given.